Spinach Plants Favor the Absorption of K+ over Na+ Regardless of Salinity, and May Benefit from Na+ When K+ is Deficient in the Soil - Jorge F. S. Ferreira; Jaime Barros da Silva Filho; Xuan Liu; Devinder Sandhu (Plants, 2020)
Two spinach (Spinacea oleracea L.) cultivars were evaluated for their response to deficient (0.25 mmolc L−1 or 0.25 K) and sufficient (5.0 mmolc L−1 or 5.0 K) potassium (K) levels combined with salinities of 5, 30, 60, 90, and 120 mmolc L−1 NaCl. Plants substituted K for Na proportionally with salinity within each K dose. Plants favored K+ over Na+, regardless of salinity, accumulating significantly less Na at 5.0 K than at 0.25 K. Salinity had no effect on N, P, and K shoot accumulation, suggesting that spinach plants can maintain NPK homeostasis even at low soil K. Ca and Mg decreased with salinity, but plants showed no deficiency. There was no Na+ to K+ or Cl− to NO3− competition, and shoot biomass decrease was attributed to excessive NaCl accumulation. Overall, ‘Raccoon’ and ‘Gazelle’ biomasses were similar regardless of K dose but ‘Raccoon’ outproduced ‘Gazelle’ at 5.0 K at the two highest salinity levels, indicating that ‘Raccoon’ may outperform ‘Gazelle’ at higher NaCl concentrations. At low K, Na may be required by ‘Raccoon’, but not ‘Gazelle’. This study suggested that spinach can be cultivated with recycled waters of moderate salinity, and less potassium than recommended, leading to savings on crop input and decreasing crop environmental footprint.